Visualization and measurement of separation positions around rotating dimpled ball - Kim, H.; Onuki, M.; Kishibe, S.; Tatani, R.; Sakaue, S.; Arai, T. (Procedia Engineering, 2012)
Flow fields around balls used for ball games have very complicated and interesting physics because most of the balls fly near critical Reynolds number. However, the mechanism of separation flow around a dimpled ball including boundary layer transition has not been fully understood, especially when the ball is rotating, because the flow is three dimensional. In the present research, the authors visualized the separated flow using smoke wire and measured flow field using hot wire to clarify separation positions around a rotating dimpled ball. Furthermore, two experimental results are compared with each other and showed a good qualitative agreement on separation positions. In addition, the movement of separation positions depending on the conditions of uniform flow velocities and non dimensional spin parameters is clarified.